Archaeology Field Schools in Nunavut - Ulujuk Zawadski, Krista; Chemko, Ericka (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2022)
Inuit have contributed to museum collections for centuries, first through ethnographic collecting for early explorers, and later for traders, whalers, and government officials. Inuit have also contributed to collections through archaeological work as field assistants, archaeologists and through field schools. Archaeological field schools in Nunavut have trained young Inuit in archaeological field methods and community collaboration since the 1990s and into the early 2000s. Building on the field schools in Iglulik in the 1990s, archaeological work with Inuit communities in Nunavut since 1999 fostered the concepts of Indigenous archaeology early in the history of field schools in Nunavut. In this paper, Krista Ulujuk Zawadski and Ericka Chemko share their experiences on field schools that took place in Nunavut as organized by the Inuit Heritage Trust Inc. (IHT) from 2002-2008 through discussions and personal reflections, offering insight into the field schools and Inuit contributions to contemporary Arctic archaeology and anthropology.